Community Service as a Driving Force for MSME Empowerment in a Sustainable Economic Ecosystem - Bambang Irawan; Suherlan; Valentino Aris (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2026)
Community service is one of the strategic pillars of the higher education Tri Dharma that holds significant potential in promoting the empowerment of Micro, Small, and Medium Enterprises (MSMEs) as the foundation of a sustainable economic ecosystem. This study aims to expand and enrich scholarly references on community service by examining its role as a driving force for MSME empowerment within the framework of sustainable economic development. The research employs a literature review method using a qualitative approach and descriptive analysis. Data were collected from Google Scholar and selected credible websites, covering publications from 2014 to 2026. Of the 50 articles initially identified, a rigorous selection process based on relevance, methodological quality, and source credibility resulted in 31 articles being analyzed further. The findings indicate that community service significantly contributes to enhancing MSME capacity through the strengthening of human capital, social capital, business innovation, and the integration of economic, social, and environmental sustainability principles. This study confirms that community service functions as a strategic instrument in building an inclusive, resilient, and sustainable MSME ecosystem.